Influence of mineral fertilizers and presowing treatment of seeds on the formation of physical features of dough and baking indices of grains of soft winter wheat - Герман, М. М. (Scientific Progress & Innovations, 2012)
The article describes the results of three-year study of influence of mineral fertilizing and pre-sowing treatment of seeds on the formation of physical features of dough and baking indices of grains of soft winter wheat. Influence of pre-sowing treatment of seeds by the growth regulator and bacterial preparations on the background fertilizers N25P25K25, N50P50K50, N75P75K75 has been observed. It is characterized by high indicators of steadiness and resistibility of dough, a weak ability of dilution and a high valorimetric estimation. The research has proved the increase of bread volume using presowing treatment of seeds by preparations polymixobacterin (150 ml/t) and diazophit (150 ml/t).